2015
DOI: 10.5812/ijhrba.24419
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Administration of High Doses of Nandrolone Decanoate on the Pituitary-Gonadal Axis in Male Rats

Abstract: Background:Anabolic-androgenic steroids (AAS) are abused by athletes.Objectives:The present study was designed to evaluate chronic administration of high doses of nandrolone decanoate (ND) on the pituitary-gonadal axis and hematological parameters in normal male rats.Materials and Methods:Thirty Wistar-Albino male rats were divided assigned to control (C), placebo (P) and test (T) groups (n = 10). Group T received 15 mg/kg intramuscular (IM) ND for eight weeks. Group P received the same volume of peanut oil, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
4
2
0
1
Order By: Relevance
“…It has been established that exercise and high doses of ND may influence the hypothalamic–pituitary–gonadal axis . In particular, it has been suggested that chronic administration of ND decreases levels of LH and follicle‐stimulating hormone, which then lead to decreased endogenous testosterone production and decreased spermatogenesis in male rats .…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…It has been established that exercise and high doses of ND may influence the hypothalamic–pituitary–gonadal axis . In particular, it has been suggested that chronic administration of ND decreases levels of LH and follicle‐stimulating hormone, which then lead to decreased endogenous testosterone production and decreased spermatogenesis in male rats .…”
Section: Discussionsupporting
confidence: 50%
“…It has been established that exercise and high doses of ND may influence the hypothalamic-pituitary-gonadal axis [23,24]. In particular, it has been suggested that chronic administration of ND decreases levels of LH and follicle-stimulating hormone, which then lead to decreased endogenous testosterone production and decreased spermatogenesis in male rats [23,24]. Low levels of LH may contribute to low levels of testosterone production as LH stimulates testosterone production in Leydig cells, and this could explain the results obtained in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Decreasing of the serum levels of LH and FSH hormones after treatment with nandrolone appeared as a consequence of inhibition of the hypothalamo–pituitary–gonadotropic axis as well. This result is consistent with the literature data (Nagata et al, 1999; Shahraki et al, 2015), although some opposite findings also exist, for example, the report by Bijlsma et al, who suggested that treatment with nandrolone did not change the level of LH hormone (Bijlsma et al, 1982). In our study, swimming training decreased insignificantly the serum level of LH hormone, which is in line with results from Manna et al (2003).…”
Section: Discussionsupporting
confidence: 91%
“…Misuse of AASs may also cause left ventricular hypertrophy with a disproportional accumulation of extracellular collagen and consequential fibrosis (Tanno еt al., 2011; Hassan & Kamal, 2013; Sretenovic et al, 2016). Administration of AASs in high doses can cause a certain degree of testicular atrophy (Naraghi et al, 2010; Mohamed & Mohamed, 2015; Takahashi et al, 2004), ultrastructural changes in the testicles (Rocha et al, 2007), and lower circulating testosterone levels but can also affect the hypothalamic–pituitary–gonadal axis (HPG axis), in the sense of lowering the follicle-stimulating hormone (FSH) levels and the luteinizing hormone (LH) levels (Nagata et al, 1999; Naraghi et al, 2010; Ferrari et al, 2013; Mohamed & Mohamed, 2015; Shahraki et al, 2015; Takahashi et al, 2004). As previously observed, misuse of the AASs may lead to higher risks of the inception of the prostate cancer as well as the erectile dysfunction (Ferrari et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Στην παρούσα μελέτη φαίνεται να αυξάνεται το ολικό βάρος των ζώων κατά τη διάρκεια της αποτοξίνωσης, ένα φαινόμενο που καταγράφεται επίσης και από τους αθλητές. Συγκεκριμένα, μια 25% αύξηση του βάρους του σώματος κατά την αναφερόμενη περίοδο παρατηρήθηκε λόγω της μακράς αναβολικής δράσης της νανδρολόνης, η οποία έγινε εμφανής μετά το τέλος της χορήγησης[138]. Ο μηχανισμός με τον οποίο προκαλείται η νεφροτοξική δραστηριότητα αποτελεί μια ενδιαφέρουσα ερώτηση.…”
unclassified